Common Causes Of Red Eye In Patients Presenting To An Ophthalmology Department Conjunctivitis, Keratitis, Uveitis - Zeeshan Tahir, Muhammad; Rafiq, Muhammad; Khan, Jehanzeb; Waseem , Muhammad; Hamza, Syed Amir; Sultan, Maria (Journal of Neonatal Surgery, 2025)
Background: Red eye is commonly seen in the clinic setting, with conditions ranging from the comparatively harmless conjunctivitis to more threatening Conditions Such as Keratitis and uveitis, which can lead to vision loss. Distinguishing between these conditions is essential to ensure prompt management and improve referral accuracy. Knowledge of local epidemiology allows clinicians to fine-tune the diagnostic process and practice epidemiologically based medicine as efficiently as possible, particularly in ophthalmology with scarce resources. Objectives: To assess the prevalence of conjunctivitis, Keratitis, and uveitis among patients presenting with a red eye, and to evaluate the clinical characteristics, demographics, and primary risk factors that enable early diagnosis, and to analyze the clinical features. Methodology This Cross Sectional Study Conducted at Department of Ophthalmology, Gajju Khan Medical College Swabi From Jan 2023 To Jan 2024.Patients with unilateral or bilateral red eyes were included once informed consent was obtained. Data were collected on patients' demographics, clinical features, visual acuity, and clinical risk factors. A slit lamp examination, fluorescein staining, and anterior chamber were performed to diagnose conjunctivitis, Keratitis, or uveitis. If needed, intraocular pressure and fundus examinations were performed. SPSS version 24 was used to analyze the data, and frequencies, means, chi-square tests, and p-values were computed at an alpha of 0.05. Results: A total of one hundred patients with red eyes were assessed. Diagnoses of conjunctivitis were most common (57%). This was followed by keratitis (25%) and then uveitis (18%). Allergic conjunctivitis was most prevalent (40%). For the cases of keratitis, 64% (most were due to an infection), and 22% of the cases were trauma-related. The majority of uveitis cases were anterior (83%) with 17% being of the systemic disease type. Pain and photophobia were strongly associated with keratitis and uveitis (p < 0.001). Increased discharge was strongly correlated with conjunctivitis (p < 0.001). Most of the conjunctivitis cases improved quickly, however, keratitis needed advanced aggressive antivirals to resolve. Conclusion: The most common cause of red eyes is conjunctivitis; however, Keratitis and uveitis also significantly contribute to morbidity. There is a much higher likelihood of better outcomes with early diagnosis, understanding of risk factors, and appropriate, timely intervention